Satellite observations showed a negligible reduction in NO2 pollution due to COVID-19 lockdown over Poland - Ugboma, Emeka A.; Stachlewska, Iwona S.; Schneider, Philipp; Stebel, Kerstin (Frontiers in Environmental Science, 2023)
The tropospheric column NO2 from the Sentinel-5P/TROPOMI (2018-2020) and Aura/OMI (2010-2020) radiometers over the Poland domain and notably for 7 major Polish cities were used to assess the annual variability and the COVID-19 lockdown effect. On a national scale during COVID-19, the most active sources of pollution were found in Katowice and Warszawa, and at the power plant in Bełchatów. For the selected Polish cities, the relative change between the monthly mean OMI NO2 values in 2020 and the reference average of 2010–2019 revealed a drop in concentrations during that year. The drop was strongest in June, i.e., for Warszawa 81%, 80% in Białystok, 40% in Katowice, 58% in Łódź, 22% in Kraków, and 35% in Wrocław, except for Gdańsk (24% increase). We show that a gradual drop in NO2 values between March and June is typical for all cities and the entire domain of Poland, being a part of the typical annual NO2 cycle. Moreover, the 2020 NO2 drop is within typical monthly and annual variability. NO2 pollution decrease was not significantly stronger than the long-term year-to-year variability derived from OMI tropospheric column NO2 (2010-2019). The TROPOMI NO2 percentage change across the cities showed that between March and June 2020, there was no consistent pattern of decreasing values observed in each city. The city with the largest reduction rate in March was Kraków. The reduction in values was observed in Gdańsk, Wrocław, and Warszawa every month. In March, several factors, including wind speed and direction, temperature, and increased emission sources, can limit the dispersion and removal of NO2. While meteorological conditions have a significant impact on the annual cycle of columnar NO2 in Poland, it's important to note that anthropogenic emissions remain the primary driver of NO2 concentrations. Therefore, the study concludes that the effect of COVID-19 restrictions on columnar NO2 pollution is negligible, and clarifies the current understanding of the COVID-19 effect over Poland, with emphasis on hotspots in the major Polish cities and their vicinity. The reduction in columnar NO2 pollution is expected to be seen in cities due to reduced traffic (domestic, municipal, and airborne).